„Wychowawca! O jakaż wzniosła musi to być dusza!” Prywatne guwernantki dziewcząt w czasach stanisławowskich - Kowalczyk, Małgorzata Ewa; Janicka, Jowita (Biuletyn Historii Wychowania, 2018)
In Stanislaw August Poniatowski’s time, the upbringing and education of wealthy noblewomen were commonly entrusted to foreign governesses. There was a strong conviction in the Polish-Lithuanian Commonwealth that command of foreign languages was the foundation of proper and careful upbringing of young women. Many parents were not discerning clients when it came to selecting a governess. Oftentimes, foreign origin sufficed. As a result of attaching so much importance to command of foreign languages accompanied by acquiring foreign manners, costumes and customs, young Polish women grew indifferent to their mother tongue, native culture and traditions. There was also a lack of sense of responsibility for the country’s future.